Fatty acid profiling of benthic harpacticoid (Pararobertsonia sp.) exposed to environmental stresses - Kassim, Zaleha; John, Akbar; Asgnari, Hidayah; ., Al-Aama; M. A. M., Fuad (Malaysian Society of Applied Biology, 2014)
Effect of various environmental stresses on the fatty acid (FA) profile of benthic harpacticoid copepod (Pararobertsonia sp.) was checked In vitro. Samples were exposed to different pH (5, 7 and 9) and salinity (15, 20, 25, 30 and 35 ppt) at constant temperature 25ºC for 30 days. After the treatment, different fatty acid levels were determined using Gas Chromatography and Mass Spectrometry (GC-MS). Results clearly indicated the positive influence of the combined effect of environmental parameter on the fatty acid content in experimental samples. The detected FAs were ranging from C5-24. Palmetic and oleic acids were in higher percentage in all the experiments. Results clearly indicated that pH7:25ppt & 35ppt at 25ºC ambient water temperature would help in producing copepods (Pararobertsonia sp.) that expresses rich fatty acid profile with high EPA/DHA ratio.